Pentingnya Classroom Management Techniques dalam Meningkatkan Kaktifan Belajar Siswa - Yusriah, Atma; Nur Azisah, Syahyani; Fadillah, Nurul (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2024)
Classroom management techniques are fundamental in creating an effective learning environmentand enhancing student engagement. This paper examines the role of classroom management inpromoting active learning among students. The study employed a qualitative research approach tocollect data through questionnaires, teacher and student interviews, and classroom observations.The results indicate that effective classroom management significantly boosts student participationand engagement. The study discusses various strategies, including physical classroom arrangement,time management, motivational strategies, positive reinforcement, and handling disruptions.Recommendations for educators to improve their classroom management skills and further researchdirections are provided.